Distribution of Total Suspended Solids Concentration in a River - Asyhar, Ahmad H.; Widodo, Basuki (IPTEK The Journal for Technology and Science, 2012)
Disposal of either industrial or nonindustrial wastewater into a river has a potential to cause river pollution. Because each load of wastewater discharged into a river contains physical, chemical, and biological parameters that determine water quality, so that it can affect the dissolved oxygen concentration in a river. Therefore the conducted research was aimed to determine the pattern of pollutant dispersion in Surabaya River within the section that is closed to the Karang Pilang Monitoring Station - Surabaya. Parameter used in this research was Total Suspended Solids (TSS). The method used was the finite volume method with Quadratic Upwind Interpolation Convective Kinematics (QUICK) scheme by means of developing models of dispersion water pollutants in a river. The governing equation was controlled by the laws of mass conservation, momentum conservation, and pollution transport equation. Further, these equations were solved using numerical calculation and followed by numerical simulation. From the numerical simulation results, it can be concluded that the magnitude of pollutant dispersion is determined by the initial discharged TSS concentrations into the river, however the longitudinal direction is more dominantly influenced than in lateral directions.